Promotion Ban and Heterogeneity in Retail Prices during the Great Lockdown - Jean Hindriks; Leonardo Madio; Valerio Serse (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We study the impact of the Belgium lockdown on retail prices using a unique dataset tracking daily prices and promotions for various products in different stores and retail chains. Two distinctive features of our analysis are the ban on promotions during the first two weeks of the lockdown, and the presence of local pricing retail chains (LP) competing with uniform (national) pricing retail chains (UP). We decompose the price changes into the regular price, the frequency, and the size of promotions. The sale price (i.e., the price paid by consumer purchasing on “sale”) increased by 7% within two weeks and by 2.5% within three months. We then provide an heterogeneity analysis of the regular price variation across stores, retailers, products, and over time. We show that LP chains reacted the most to the lockdown with spatial heterogeneity. The heterogeneity in price response also suggests that the price increase was not driven by cost inflation.
Keywords: D22; E30; E31; L11; 330; Covid-19; pricing; lockdown; retailers